[Corruption at NAIA ; Broadcast City ; Anna Villadolid [videorecording] - Lazaro, Cheche (The Probe Team, 1988)
Tackles graft and corruption in the Bureau of Customs; controversies in BBC, RPN, IBC television stations; and interview with Ana Villadolid, a classical ballet dancer.